2014
DOI: 10.21640/ns.v6i11.87
|View full text |Cite
|
Sign up to set email alerts
|

Oligopsony-Oligopoly The perfect imperfect competition

Abstract: Oligopoly and oligopsony have been studied extensively. However, the dual figure of the oligopsonistic-oligopolistic intermediary has not been. This dual personality has a double negative impact on the market, on one hand reduces the demand to producers who face a competitive market, lowering prices as buyers, and on the other hand reducing its offer by raising the prices as sellers. In this way, their benefits are increased buying cheap and selling expensive, affecting effective demand of the consumer and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In 2010 I broadened these analyses and wrote them in an article published in Spain [2]. In the year 2013 I applied those first analysis to the oligopsony 3 -oligopoly 4 figure [3] and observed that although there is some competition in the second figure, the results for both, the seller (the producer of the goods) and the final consumer, are like those of the monopsony-monopoly figure. It is therefore of the utmost importance that the na-1 Monopsony: market in which there is only one buyer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010 I broadened these analyses and wrote them in an article published in Spain [2]. In the year 2013 I applied those first analysis to the oligopsony 3 -oligopoly 4 figure [3] and observed that although there is some competition in the second figure, the results for both, the seller (the producer of the goods) and the final consumer, are like those of the monopsony-monopoly figure. It is therefore of the utmost importance that the na-1 Monopsony: market in which there is only one buyer.…”
Section: Introductionmentioning
confidence: 99%
“…2 Monopoly: market in which there is only one seller. 3 Oligopsony: market in which there are few buyers. 4 Oligopoly: market in which there are few sellers.…”
Section: Introductionmentioning
confidence: 99%